2007
DOI: 10.48550/arxiv.0704.2769
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards a Background Independent Quantum Gravity in Eight Dimensions

J. A. Nieto

Abstract: We start a program of background independent quantum gravity in eight dimensions. We first consider canonical gravity a la "Kaluza-Klein" in D = d + 1 dimensions. We show that our canonical gravity approach can be applied to the case of self-dual gravity in four dimensions. Further, by using our previously proposed classical action of Ashtekar self-dual gravity formalism in eight dimensions, we proceed to develop the canonical approach in eight dimensions. Our construction considers different SO(8) symmetry br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…But the curvature tensor R a 1 a 2 µ 1 µ 2 contains only the two indices a 1 and a 2 . This is one of the reason why in Refs [6]- [9] an Ashtekar formalism with an octonionic structure was proposed. Although this an interesting route here we shall follow an alternative approach.…”
Section: -Ashtekar Formalism In 8-dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…But the curvature tensor R a 1 a 2 µ 1 µ 2 contains only the two indices a 1 and a 2 . This is one of the reason why in Refs [6]- [9] an Ashtekar formalism with an octonionic structure was proposed. Although this an interesting route here we shall follow an alternative approach.…”
Section: -Ashtekar Formalism In 8-dimensionsmentioning
confidence: 99%
“…Higher dimensional Ashtekar formalism has shown to be a promising proposal [1][2][3][4][5] (see also Ref. [6][7][8][9][10]). The main physical reason for this is that it allows a possible connection with string theory [11]; an alternative approach for quantum gravity.…”
Section: -Introductionmentioning
confidence: 99%
“…The general believe is that self-dual gravity makes sense only in four dimensions since in this case the dual of a two form (the curvature) is again a two form. However, there are a number of evidences that self-dual gravity can also be implemented in eight dimensions [5]- [8]. It turns out that even in four dimensions self-dual gravity does not determine the signature of the 'space-time'.…”
Section: -Introductionmentioning
confidence: 99%
“…This seems to indicate that, from a quantum gravity perspective, 4-dimensions is an exceptional signature. However, in references [4][5][6][7] it is shown that also makes sense to consider self-dual gravity in 8-dimensions, but one should define * R AB in terms of the η-symbol. (see Refs.…”
mentioning
confidence: 99%
“…Here, Ê i (a) is an operator associated with the E (a) i part of the general vielbein on a M D -manifold (see Ref. [7] and references therein)…”
mentioning
confidence: 99%